Розробка системи забезпечення ресурсоенергозберігаючого експлуатаційного режиму роботи асинхронного електродвигуна - Квітка, С. О.; Вовк, О. Ю.; Волошина, А. А.; Стребков, О. А. (Енергетика і автоматика, 2017)
DEVELOPMENT OF THE SYSTEM TO ENSURE RESORCINARENE-EFFICIENT OPERATING MODE OF THE ASYNCHRONOUS MOTORS. Kvitka, A. Vovk, A. Voloshina, A. Strebkov In Ukraine there is a national economic problem of resourceenergysaving in the electric motors used in agriculture.The problem is that the operational reliability of asynchronous motors in agriculture remains low due to the large amount of negative operational impacts. In addition, under variable load machines, there is wasteful power consumption drive motorsTherefore, the necessary scientific and technical solutions in the field of energy saving, and improve the operating reliability of drive asynchronous motorsLosses of electric energy in the asynchronous motor and consumption of resources are closely related, but the assessment of electric energy losses is carried out in units of electric energy and resource costs of insulation – in terms of insulation degradation. Consequently it is difficult to evaluate the overall operating modes of asynchronous motors.Therefore, the development of the methodology of the unified energy performance assessment modes asynchronous motor and on its basis development of a system to ensure resources and energy saving operational mode of the latter is the actual problem.The purpose of research – improving the reliability of the asynchronous motors and the reduction of active power losses in it.The materials and methods of research. For the assessment of electric energy losses in asynchronous motor and costs resource insulation design methodology was developed a unified energy estimation of operating modes of electric motors.Was taken, as in the manufacture of the stator windings of an asynchronous motor consumes a significant amount of electrical energy, the consumption of resource of electric motor windings can be equivalently expressed in quantity of consumed electrical energy on the production and installation of windings assigned to one base hour resource isolation.To assess operational mode of the motor is expressed in equivalent consumption of the resource in the cost of electrical energy, consisting of losses of active energy in the motor and the equivalent costs of electric energy due to thermal wear of the insulation structure.The result of the research, the mathematical model of resources and energy saving mode of the asynchronous motor, the variant which is given on the example of the drive machine with linearly increasing mechanical characteristics.The microprocessor system receives signals from the motor and analyzes its operating mode according to the proposed algorithm, and then changes the value supplied to the motor voltage to the optimum value, providing resources and energy saving mode of operation of the asynchronous motor, i.e. reducing specific losses of electric energy.ConclusionDeveloped system of ensure resources and energy saving operational mode of the asynchronous motor can reduce the power losses at partial load of the working machine. For example, when the load factor of the working machine is 0,9, reducing the ratio of supplied voltage to 0,8, power losses in the motor are reduced by 38 %.